The contributions of the Khorezm enlighteners to the development of our nation and homeland - Rustamovich, Kutlimuratov Sardorbek (Dynamics of Politics and Democracy, 2023)
Purpose: This study aims to explore the contributions of the Khorezm Jadids to the advancement of national independence, education, culture, and socio-political development in Uzbekistan, highlighting their pioneering role in modernizing schools, literature, and public consciousness during the late 19th and early 20th centuries. Research methodology: The research adopts a multidisciplinary approach, integrating historical-analytical, philosophical-comparative, and source-based methods. It utilizes archival records, memoirs, scholarly literature, and press materials to reconstruct the origins, activities, and influence of the Jadid movement within the cultural and political context of Turkestan. Results: The findings reveal that the Khorezm Jadids were instrumental in promoting democratic reforms, national identity, and the spread of modern education and journalism. Despite facing resistance from conservative forces and colonial oppression, their ideas influenced successive enlightenment movements and shaped Uzbekistan’s modern intellectual and political landscape. Conclusion: The study underscores the pivotal role of the Jadids in establishing foundational institutions of modern Uzbekistan—such as the first modern schools, newspapers, novels, and democratic ideals—emphasizing the need for continuous scholarly engagement with their legacy. Limitations: This research is limited to textual and historical sources without extensive use of oral histories or ethnographic methods, potentially omitting local perspectives and interpretations. Contribution: This article provides a deeper understanding of Jadidism’s intellectual, cultural, and political relevance, offering new insights into its impact on Uzbekistan’s national awakening and its enduring significance in contemporary educational and ideological discourse.